Realization of introducing non-woven veil on interlaminar radial strength of Glass Epoxy L-Bend composites (Fracture and Structural Integrity, 2025)
This study investigates the effect of interleaving non-woven veils and their surface areal density on the curved beam strength (CBS) and interlaminar radial stress (ILRS) of glass/epoxy L-bend composite laminates. Carbon veils with areal densities of 15, 20, and 30 g/m2 , and glass veils with 25 and 30 g/m2 were used as interleaving materials. The L-bend laminates, both interleaved and non-interleaved, were fabricated using the compression moulding technique. A four-point bending test was employed to evaluate the influence of veil interleaving and areal density on CBS and ILRS. The experimental results demonstrated that interleaving with carbon and glass non-woven veils significantly affects the performance of curved laminates. Notably, the CBS of the glass/epoxy laminate improved by 88% and 17% for specimens interleaved with 15 g/m2 carbon and 30 g/m2 glass veils, respectively. Furthermore, the ILRS of carbon veil-interleaved laminates showed a strong dependence on the veil’s areal density. In contrast, interleaving with glass veils did not exhibit a significant effect on ILRS. Finally, the fracture surfaces of the tested laminates were examined using scanning electron microscopy (SEM) to identify the various failure modes in the curved region and to understand the underlying fracture mechanisms.
Keywords: Non-woven veils; curved beam; curved beam strength; interlaminar radial stress; delamination mitigation